(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
The article presents an analysis of studies conducted on the Voghjaberd landslide. For the first time, the authors gave a classification type of the Voghjaberd landslide was proposed suggested, the mechanism of landslide processes and the absence of one or several sliding surfaces and horizontal displacements was justified. It was noted that landslides in the study area are associated with subsidence of soils. The causal relationship between the presence of groundwater and subsidence of soils is given.